Spatial and Temporal Variation/ Variability of the Estimated and Measured Soil Moisture in Northern Jordan - Zeitoun, Mohammad; Al-Maqbel, Ali; Alkalaf, Rawan (Dirasat: Human and Social Sciences, 2023)
The study employed the adjusted Thornthwaite-Mather model (1955) to estimate soil moisture in Irbid, Ras Muneef, and Almafraq stations for the period (1977-2015). Besides, fieldwork to collect soil moisture from 22 sites for four months (November 2019 to February 2020) was conducted. The results show that both estimated and observed soil moisture increased toward the northwest of the study area, that the highest average soil moisture reached 196.8 mm in February in Ras Munif following rainfall and soil characteristics such as texture, porosity, permeability, and soil water capacity. In addition, the content of soil moisture tends to be more stable when the soil is at or near its field capacity. However, the instability of soil moisture decreases when the soil is dry, Soil moisture reaches its lowest level from May to October, and the lowest average moisture is recorded in October at a rate of up to 0.5 mm, in Mafraq. It has also been found that the soil moisture in the northwest slopes is slightly higher than those in the northeast slopes. The annual mean of true evapotranspiration ranged between (5.4 and 54 mm); The highest annual averages were recorded in Irbid Station for all months, which exceeded the other stations; It reached (40 mm) in the year 2009. Ultimately, the study recommended that it is necessary to integrate different studies such as agro-meteorological, hydrological, and studies to establish a geodatabase to support future agricultural planning.